Structural characterization of self-assembled chain like Fe-FeOx Core shell nanostructure - Mukhtar, Aiman (Nanoscale Res Lett, 2019)
One of the big challenge of studying the core-shell iron nanostructures is to know the nature of oxide shell, i.e., whether it is γ-Fe(2)O(3) (Maghemite), Fe(3)O(4) (Magnetite), α-Fe(2)O(3) (Hematite), or FeO (Wustite). By knowing the nature of iron oxide shell with zero valent iron core, one can determine the chemical or physical behavior of core-shell nanostructures. Fe core-shell nanochains (NCs) were prepared through the reduction of Fe(3+) ions by sodium boro-hydride in aqueous solution at room atmosphere, and Fe NCs were further aged in water up to 240 min. XRD was used to study the structure of Fe NCs. Further analysis of core-shell nature of Fe NCs was done by TEM, results showed increase in thickness of oxide shell (from 2.5, 4, 6 to 10 nm) as water aging time increases (from 0 min, 120 min, 240 min to 360 min). The Raman spectroscopy was employed to study the oxide nature of Fe NCs. To further confirm the magnetite phase in Fe NCs, the Mössbauer spectroscopy was done on Fe NCs-0 and Fe NCs-6. Result shows the presence of magnetite in the sample before aging in water, and the sample after prolonged aging contains pure Hematite phase. It shows that prolonged water oxidation transforms the structure of shell of Fe NCs from mixture of Hematite and Magnetite in to pure hematite shell. The Magnetic properties of the Fe NCs were measured by VSM at 320 K. Because of high saturation magnetization (Ms) values, Fe NCs could be used as r(2) contrasts agents for magnetic resonance imaging (MRI) in near future. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-019-3128-2) contains supplementary material, which is available to authorized users.